Morphological and Molecular Characterization of Nothotylenchus medians and N. similis (Nematoda: Anguinidae) from Southern Alberta, Canada - Maria Munawar; Atta Ur Rahman; Pablo Castillo; Dmytro P. Yevtushenko (Horticulturae, 2022)
The nematode family, Anguinidae, is a diverse group of polyphagous nematodes, generally known as fungal feeders or parasites of aerial plant parts. Here, we present the morphological and molecular characterization of adult females of two Nothotylenchus species, N. medians and N. similis, along with host association and geographical distribution data of the genus. Both species are recorded as new reports from Canada and designated as reference populations for future studies. Morphological or morphometrical variation was not observed in the Canadian population of N. medians and N. similis, in comparison with the original description. Phylogenetic analyses based on 18S and D2–D3 of 28S genes placed both species within Anguinidae. Since the biology of the genus Nothotylenchus has not been rigorously characterized, the habitat and distribution information presented in this study will shed some light on the ecology of these nematodes. Notably, the detection of N. medians and N. similis in our nematode inventory survey indicates that considerable Nothotylenchus diversity is hidden in these soils. Consequently, increased surveys and more in-depth research are needed to explore the full diversity of anguinids inhabiting these cultivated areas.